Persepsi Masyarakat terhadap Manfaat Lansekap Mangrove Center Tuban Kabupaten Tuban Provinsi Jawa Timur - RAHMAN, DIMAS SAIKHU; KOHDRATA, NANIEK; MAYUN, IDA AYU (Jurnal Arsitektur Lansekap; Vol.2, No.2, Oktober 2016DO - 10.24843/JAL.2016.v02.i02.p01, 2016)
ABSTRACT A Public Perception towards Benefits of the Landscape of Mangrove Center Tuban Tuban Regency - East Java Province This research was motivated by the problems that are often experienced by the manager of Mangrove Center Tuban changing the function of the region in this area which is the Environmental Educatian Center. This research uses descriptive qualitative approach with case studies in order to capture the phenomena that exist in the field then studied more deeply. The highest perception of knowledge of the benefits and advantages of mangrove forests in Mangrove Center Tuban rated public of the environmental aspects of the lowest 40% and the perception that the social aspects of the environment of 3%. Highest perception Mangrove Center Tuban by 40% of respondents perceived as the cultivation of mangrove and lowest perception is envorinmental education center at 14%. The highest perception of respondents stated assess the mangrove forests of the aspects of a life by 63% and the lowest was the respondent state on the features and functions of mangrove forests of 3%. The highest expression of respondents said getting information from the mass media by 37% and the lowest statement from the manager only by 29%. The conclusion of this study is the public perception of mangrove forests Mangrove Center Tuban is people just look at the circumstances that they see without looking for information first.